Bimetallic Zeolitic Imidazolite Framework Derived Carbon Nanotubes Embedded with Co Nanoparticles for Efficient Bifunctional Oxygen Electrocatalyst. Issue 9 (4th December 2017) - Li, Yinle; Jia, Baoming; Fan, Yanzhong; Zhu, Kelong; Li, Guangqin; Su, Cheng‐Yong
Abstract: Bifunctional oxygen catalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) with high activities and low‐cost are of prime importance and challenging in the development of fuel cells and rechargeable metal–air batteries. This study reports a porous carbon nanomaterial loaded with cobalt nanoparticles (Co@NC‐ x / y ) derived from pyrolysis of a Co/Zn bimetallic zeolitic imidazolite framework, which exhibits incredibly high activity as bifunctional oxygen catalysts. For instance, the optimal catalyst of Co@NC‐3/1 has the interconnected framework structure between porous carbon and embedded carbon nanotubes, which shows the superb ORR activity with onset potential of ≈1.15 V and half‐wave potential of ≈0.93 V. Moreover, it presents high OER activity that can be further enhanced to over commercial RuO2 by P‐doped with overpotentials of 1.57 V versus reversible hydrogen electrode at 10 mA cm −2 and long‐term stability for 2000 circles and a Tafel slope of 85 mV dec −1 . Significantly, the nanomaterial demonstrates better catalytic performance and durability than Pt/C for ORR and commercial RuO2 and IrO2 for OER. These findings suggest the importance of a synergistic effect of graphitic carbon, nanotubes, exposed Co–N x active sites, and interconnected framework structure of various carbons for bifunctional oxygen electrocatalysts. Abstract : A porous carbon nanomaterial (Co@NC‐ x / y ) embedded with cobalt nanoparticles and rooted with nanotubes derived from pyrolysis of a Co/Zn bimetallic zeolitic imidazolite framework is reported. The optimal catalyst of Co@NC‐3/1 shows the superb oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) activities. And its mechanism is thoroughly discussed.